Anatomy of the normal fetal heart: The basis for understanding fetal echocardiography - Beatriz Picazo-Angelin; Juan Ignacio Zabala-Argüelles; Robert H Anderson; Damian Sánchez-Quintana (Annals of Pediatric Cardiology, 2018)
The rapid changes that have taken place in recent years in relation to techniques used to image the fetal heart have emphasized the need to have a detailed knowledge ofnormal cardiac anatomy. Without such knowledge, it is difficult, if not impossible, to recognize the multiple facets of congenital cardiac disease. From the inception of fetal echocardiographic screening, the importance of basic knowledge of cardiac anatomy has been well recognized. The current machines used for imaging, however, now make it possible potentially to recognize features not appreciated at the start of the specialty. So as to match the advances made in imaging, we have now revisited our understanding of normal cardiac anatomy in the mid-gestational fetus. This was made possible by our dissection of 10 fetal hearts, followed by production of addition histological sections that mimic the standard ultrasound views. The fetuses ranged in gestational age from between 20 and 28 weeks. We then correlated the obtained anatomic images with the corresponding ultrasonic images used in the standard fetal screening scan. We also interrogated the anatomic sections so as to clarify ongoing controversies regarding detailed features of the normal cardiac anatomy. We have been able to show that the views now obtained using current technology reveal many details of anatomy not always appreciated at earlier times. Knowledge of these features should now permit diagnosis of most congenital cardiac malformations. The anatomic-echocardiographic correlations additionally provide a valuable resource for both the understanding and teaching of fetal echocardiography.